Defenders and Challengers of Endothelial Barrier Function - Rahimi, Nader (Frontiers in Immunology, 2017)
Regulated vascular permeability is an essential feature of normal physiology and its dysfunction is associated with major human diseases ranging from cancer to inflammation and ischemic heart diseases. Integrity of endothelial cells also play a prominent role in the outcome of surgical procedures and organ transplant. Endothelial barrier function and integrity are regulated by a plethora of highly specialized transmembrane receptors, including claudin family proteins, occludin, junctional adhesion molecules (JAMs), vascular endothelial (VE)-cadherin and the newly identified immunoglobulin (Ig) and proline rich receptor-1 (IGPR-1) through various distinct mechanisms and signaling. On the other hand, vascular endothelial growth factor (VEGF) and its tyrosine kinase receptor, VEGFR-2, play a prominent role in the destabilization of endothelial barrier function. While claudins and occludin regulate cell-cell junction via recruitment of zonula occludens (ZO), cadherins via catenin proteins, and JAMs via ZO and afadin, IGPR-1 recruits bullous pemphigoid antigen 1 (BPAG1 also called dystonin (DST) and SPIN90/WISH (SH3 protein interacting with Nck). Endothelial barrier function is moderated by the function of transmembrane receptors and signaling events that act to defend or destabilize it. Here, I highlight recent advances that have provided new insights into endothelial barrier function and mechanisms involved. Further investigation of these mechanisms could lead to the discovery of novel therapeutic targets for human diseases associated with endothelial dysfunction.